Bathymetrically controlled velocity‐shear front at a tidal river confluence. Issue 8 (28th August 2015) - Blain, Cheryl Ann; Mied, Richard P.; McKay, Paul; Chen, Wei; Rhea, W. Joseph
Abstract Nonbuoyant front formation at the confluence of Nanjemoy Creek and the main Potomac River (MD) channel is examined. Terra satellite ASTER imagery reveals a sediment color front emerging from Nanjemoy Creek when the Potomac is near maximum ebb. Nearly contemporaneous ASTER and Landsat ETM+ imagery are used to extract surface velocities, which suggest a velocity shear front is collocated with the color front. In situ velocities (measured by RiverRay traverses near the Nanjemoy Creek mouth) confirm the shear front's presence. A finite‐element simulation (using ADCIRC) replicates the observed velocity‐shear front and is applied to decipher its physics. Three results emerge: (1) the velocity‐shear front forms, confined to a shoal downstream of the creek‐river confluence for most of the tidal cycle, (2) a simulation with a flat bottom in Nanjemoy Creek and Potomac River (i.e., no bathymetry variation) indicates the velocity‐shear front never forms, hence the front cannot exist without the bathymetry, and (3) an additional simulation with a blocked‐off Creek entrance demonstrates that while the magnitude of the velocity shear is largely unchanged without the creek, shear front formation is delayed in time. Without the Creek, there is no advection of the M6 tidal constituent (generated by nonlinear interaction of the flow with bottom friction) onto the shoals, only a locally generated contribution. A tidal phase difference between Nanjemoy and Potomac causes the ebbing Nanjemoy Creek waters to intrude into the Potomac as far south as its deep channel, and draw from a similar location in the Potomac during Nanjemoy flood.